High-strength impact-resistant weather-resistant plate and preparation method thereof
Patent Information
- Application Number
- CN202611291569.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-16
AI Technical Summary
但此类无机板材普遍存在吸水率过高的问题,部分产品的吸水率可达22%左右
本申请通过将超高分子量聚乙烯、木粉、马来酸酐接枝聚乙烯、改性稀土氧化物、氨基聚倍半硅氧烷、丁腈橡胶、润滑剂、发泡剂和助剂复配,使得板材的拉伸强度、弯曲模量和抗冲击强度提升。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of building materials technology, and more specifically, to a high-strength, impact-resistant, and weather-resistant building material and its preparation method. Background Technology
[0002] Precast insulated building panels, as a type of composite panel integrating thermal insulation and decoration functions, can be directly installed on the exterior walls of buildings. Their structural layers, from the outside to the inside (from the exterior to the wall), include a finishing layer, a composite adhesive layer, an insulation core layer, and a base layer. Among these, the finishing layer, as the structural layer directly exposed to the external environment, determines the panel's durability, safety, and decorative lifespan through its material properties.
[0003] Currently, decorative layers are mainly made from the following two materials: First, fiber cement board or calcium silicate board are the most widely used decorative materials. However, these inorganic boards generally suffer from excessively high water absorption, with some products reaching approximately 22%. High water absorption causes significant swelling and deformation in humid environments, leading to surface cracking, water seepage, and discoloration, severely impacting the building's appearance and the long-term stability of the insulation system. Furthermore, fiber cement board and calcium silicate board have poor impact resistance and are not durable. Additionally, the surface of fiber cement board or calcium silicate board typically relies on organic coatings for decoration and protection; however, these coatings are prone to aging phenomena such as chalking, fading, and loss of gloss under long-term ultraviolet radiation and acid rain erosion, significantly shortening the lifespan of the decorative finish.
[0004] Aluminum panels, another common decorative material, offer good weather resistance. However, some manufacturers use thin aluminum sheets (0.5mm to 0.8mm thick) to reduce costs, resulting in insufficient impact resistance and bending strength, making it difficult to meet exterior wall safety requirements. Furthermore, aluminum panel cladding layers are typically bonded to insulation core materials using traditional cold-bonding techniques. This process has stringent requirements for the construction environment and adhesive performance, easily leading to quality issues such as hollow areas and detachment in actual projects. Additionally, the high cost of aluminum panels themselves hinders their large-scale application.
[0005] Due to the high water absorption, swelling and deformation, cracking and water seepage, poor impact resistance, lack of durability, easy aging and powdering of organic coatings, and fading and loss of gloss of fiber cement boards and calcium silicate boards, as well as the insufficient impact and bending strength of aluminum sheets, the tendency of cold bonding process to delaminate and fall off, and the high cost, there is an urgent need to develop a surface material with high strength, strong impact resistance and good weather resistance. Summary of the Invention
[0006] In order to provide a high-strength, impact-resistant and weather-resistant finish with comprehensive performance, this application provides a high-strength impact-resistant and weather-resistant sheet material and its preparation method.
[0007] In a first aspect, this application provides a high-strength, impact-resistant, and weather-resistant sheet material, employing the following technical solution: A high-strength, impact-resistant, and weather-resistant sheet material is prepared from the following raw materials in parts by weight: 60-80 parts of ultra-high molecular weight polyethylene 20-25 parts wood flour 3-5 parts of maleic anhydride-grafted polyethylene 10-15 parts of modified rare earth oxides 0.2-0.4 parts of amino-polysilsesquioxane 10-20 parts of nitrile rubber 3-5 parts lubricant 1-2 parts of foaming agent 0-3 parts of auxiliary agent; The wood flour has an average particle size of 5-20 μm, the modified rare earth oxide has an average particle size of 1-5 μm, and the nitrile rubber has an average particle size of 15-40 μm.
[0008] By employing the above technical solution, ultra-high molecular weight polyethylene (UHMWPE) and nitrile rubber (NBR) are used synergistically. The NBR, with a particle size of 15-40 μm, is uniformly dispersed in the matrix, effectively absorbing and dissipating external impact energy through its excellent elastic deformation capability. This improves the notched impact strength and flexural modulus of the sheet, reducing the problem of easy cracking or denting deformation after impact. Simultaneously, maleic anhydride-grafted polyethylene acts as an interface compatibilizer. Its anhydride groups can interact with wood flour, while the polyethylene backbone achieves good compatibility with the UHMWPE matrix. This further improves the interfacial bonding strength between the wood flour and the matrix resin, allowing the wood flour to strengthen the skeleton and reduce costs while minimizing stress concentration and mechanical property degradation caused by interfacial debonding. Furthermore, the modified rare earth oxides are uniformly distributed in ultra-high molecular weight polyethylene with an ultra-fine particle size of 1-5μm. Their unique crystal structure and surface activity can play a role in heterogeneous nucleation, promoting the crystal refinement and orientation regularization of the ultra-high molecular weight polyethylene matrix, thereby effectively improving the tensile strength, flexural modulus and impact strength of the sheet. At the same time, rare earth elements can also enhance the weather resistance of the sheet by shielding ultraviolet rays, so that the sheet has both high strength, high impact resistance and excellent resistance to ultraviolet aging.
[0009] Amino polysilsesquioxanes endow the boards with extremely low water absorption and excellent hydrophobic properties, reducing problems such as swelling and deformation, surface cracking, and water seepage and discoloration caused by water absorption. They also effectively block the erosion of acid rain and other corrosive media. Furthermore, their introduction enhances the density and chemical stability of the boards, allowing the surface layer to maintain uniform color and stable gloss for a long time without relying on traditional organic coatings. This reduces aging problems such as chalking, fading, and loss of gloss under ultraviolet radiation and acid rain, significantly extending the decorative lifespan.
[0010] Preferably, the modified rare earth oxide is prepared by the following method: 1) Add nano-La2O3 and nano-CeO2 to a silane coupling agent ethanol solution, soak, filter, and dry to obtain pretreated nano-La2O3; 2) Mix potassium titanate whiskers, N,N-dimethylformamide and caprolactam, raise the temperature to 60-65℃, add pretreated nano-La2O3 and nano-CeO2, stir, keep warm for 1-2 hours, filter, and dry to obtain modified rare earth oxides.
[0011] By adopting the above technical solution, the surface of nano-La2O3 and CeO2 is pretreated by silane coupling agent ethanol solution, and organic functional groups are introduced on their surface to realize the transformation of nanoparticles from hydrophilic to oleophilic, thereby improving their interfacial compatibility with ultra-high molecular weight polyethylene matrix, effectively inhibiting the aggregation of high surface energy nanoparticles, and ensuring that they can be uniformly dispersed in the matrix with an ultrafine particle size of 1-5μm. Pretreated rare earth oxides and potassium titanate whiskers are treated in an N,N-dimethylformamide and caprolactam system, allowing the rare earth oxides to adhere to the surface of the potassium titanate whiskers. This structure retains the unique structure of rare earth elements, enabling heterogeneous nucleation and UV shielding, promoting the refinement and regularization of ultra-high molecular weight polyethylene crystals, and effectively absorbing and shielding ultraviolet rays. It also utilizes the high strength, high modulus, and aspect ratio of potassium titanate whiskers to further enhance the rigidity, strength, and impact toughness of the sheet. At the same time, the introduction of caprolactam can form amide groups on the surface of hybrid particles, enhancing their interfacial bonding with maleic anhydride-grafted polyethylene and ultra-high molecular weight polyethylene matrix. This allows the modified rare earth oxides to be uniformly dispersed in the matrix and fully exert the synergistic effects of UV shielding, crystallization regulation, and mechanical enhancement.
[0012] Preferably, the weight ratio of the nano-La2O3, the nano-CeO2, the potassium titanate whiskers, and the caprolactam is 10:1-2:3-5:0.6-1.
[0013] By employing the above technical solutions, nano-La2O3 as the main functional phase endows the substrate with efficient UV shielding and heterogeneous nucleation and crystal refinement capabilities. Nano-CeO2 synergistically enhances UV absorption and antioxidant weather resistance, and the appropriate ratio of the two ensures the dominant position of the rare earth functional phase. Potassium titanate whiskers exert a fiber reinforcement effect with a high aspect ratio, improving tensile strength and flexural modulus, and the appropriate amount ensures that the nano-rare earth oxides fully coat the surface, avoiding agglomeration that leads to stress concentration. Caprolactam introduces amide groups on the surface of hybrid particles, strengthening the interfacial compatibility and anchoring effect with maleic anhydride-grafted polyethylene. This ratio achieves a synergistic balance between UV shielding, mechanical reinforcement, and interfacial compatibility, ensuring that the modified rare earth oxides are uniformly dispersed in the matrix and fully exert their multifunctional synergistic effect.
[0014] Preferably, the average particle size of the potassium titanate whiskers is 1-5 μm.
[0015] Preferably, the average particle size of the nano-La2O3 is 10-100 nm, and the average particle size of the nano-CeO2 is 5-50 nm.
[0016] By employing the above technical solution, potassium titanate whiskers with an average particle size of 1-5 μm provide a rigid framework support for nano-rare earth oxides, ensuring that the hybrid structure is uniformly dispersed in the matrix and forms a three-dimensional network reinforcement system. The nano-La2O3 has an average particle size of 10-100 nm, and the nano-CeO2 has an average particle size of 5-50 nm, giving them extremely high specific surface area and surface activity, enabling them to efficiently perform heterogeneous nucleation and UV shielding functions. This particle size gradient design achieves synergistic control between the macroscopic reinforcing framework of the whiskers and the microscopic functional regulation of the nano-rare earth elements, avoiding nanoparticle agglomeration while strengthening interfacial bonding, thus comprehensively improving the mechanical properties and weather resistance stability of the substrate.
[0017] Preferably, the lubricant comprises at least one of oxidized polyethylene wax, PE wax, fatty alcohol dicarboxylic acid ester, and stearic acid.
[0018] By adopting the above technical solutions, the melt viscosity can be effectively reduced, and the flow and dispersion of ultra-high molecular weight polyethylene with fillers such as wood flour and modified rare earth can be improved during the processing.
[0019] Preferably, the wood flour is modified wood flour, which is prepared by the following method: A. Mix deionized water and ethanol, stir, add tetraethyl orthosilicate and wood flour, add ammonia dropwise until the pH is 9-10, stop adding, continue stirring for 5-6 hours, filter, take the filter residue to obtain pretreated wood flour; Pretreated wood flour is added to a cerium sulfate aqueous solution, followed by triethylamine and sodium thiosulfate. The mixture is heated to 60-65°C and kept at that temperature for 6-8 hours. After filtration and drying, modified wood flour is obtained.
[0020] By employing the above technical solution, a dense silica coating layer is formed on the surface of wood flour through the hydrolysis and condensation of tetraethyl orthosilicate under ammonia catalysis. This effectively seals the hydrophilic hydroxyl groups on the wood flour surface and reduces its hygroscopic swelling, while simultaneously improving the thermal stability and flame retardant properties of the wood flour. The pretreated wood flour is then placed in a cerium sulfate aqueous solution. Under the synergistic effect of triethylamine alkaline environment and sodium thiosulfate reducing agent, cerium ions are reduced and deposited on the surface of the silica coating layer, introducing cerium-based functional groups with UV shielding and antioxidant activity. This dual modification endows the wood flour surface with both hydrophobic protection and weather resistance. On the one hand, it significantly reduces the water absorption rate of the wood flour, avoiding moisture swelling and deformation of the board and interfacial debonding problems caused by the moisture absorption and expansion of the wood flour. On the other hand, through the UV absorption and free radical capture effect of the cerium-based groups, it synergistically enhances the weather resistance and anti-aging properties of the board. Simultaneously, the silica-cerium composite coating layer improves the interfacial compatibility between the wood flour and the ultra-high molecular weight polyethylene matrix, allowing the reinforcing skeleton effect of the wood flour to be fully utilized, achieving a balance of low cost, high performance, and long lifespan.
[0021] Preferably, in step A, the volume ratio of water to ethanol is 1:1-4, and the weight ratio of wood flour to tetraethyl orthosilicate is 1:0.05-0.1.
[0022] Preferably, the ratio of the water and ethanol mixture to the wood flour is 1g:6-8ml.
[0023] By adopting the above technical solution, the volume ratio of wood flour to ethanol can effectively reduce the hydrolysis rate of tetraethyl orthosilicate, allowing the silica coating layer to be deposited uniformly and densely on the surface of wood flour, avoiding uneven coating or agglomeration caused by excessively rapid hydrolysis. The weight ratio of wood flour to tetraethyl orthosilicate ensures a moderate coating thickness, which effectively seals the hydroxyl groups on the wood flour surface to reduce hygroscopicity, while avoiding excessive coating that could affect the interfacial bonding between the wood flour and the matrix. The ratio of the mixed liquid to wood flour provides a sufficient liquid environment to ensure uniform dispersion of the wood flour, allowing the tetraethyl orthosilicate to fully contact and react, thus improving coating efficiency and consistency.
[0024] Preferably, in step B, the ratio of the pretreated wood flour, the cerium sulfate aqueous solution, the triethylamine, and the sodium thiosulfate is 10g:90-110ml:0.4-1.5g:0.05-0.1g.
[0025] By adopting the above technical solution, a sufficient liquid environment is ensured so that cerium ions can fully contact and uniformly deposit on the surface of wood flour. Triethylamine regulates the alkalinity of the system and promotes the stable loading of cerium-based groups. Sodium thiosulfate, as a reducing agent, can reduce and activate cerium ions in small amounts and efficiently, thus achieving a dense coating of the cerium-based light-stabilized functional layer.
[0026] Preferably, the foaming agent is composed of azodicarbonamide and sodium citrate in a weight ratio of 1:0.8-1.2.
[0027] By adopting the above technical solution, azodicarbonamide decomposes upon heating to release gas and form cells. Sodium citrate acts as a synergistic additive to regulate its decomposition rate and temperature, making the foaming process mild and controllable. The combination of the two can form a uniform and dense cell structure, effectively reducing the density of the board and reducing cell collapse or merging defects, thus ensuring the mechanical strength and dimensional stability of the board while achieving lightweighting.
[0028] Preferably, the additives include at least one of antioxidants, colorants, and heat stabilizers.
[0029] By adopting the above technical solutions, antioxidants can inhibit the thermo-oxidative degradation of ultra-high molecular weight polyethylene and nitrile rubber during processing and use, thus extending the service life of the boards; colorants give the finishing layer a stable decorative color, meeting the requirements of building appearance; and heat stabilizers improve the thermal stability of the system during processing, prevent polymer degradation during high-temperature mixing and molding, and ensure the mechanical properties and appearance quality of the boards.
[0030] Secondly, this application provides a method for preparing a high-strength, impact-resistant, and weather-resistant sheet material, employing the following technical solution: A method for preparing a high-strength, impact-resistant, and weather-resistant sheet material includes the following preparation steps: S1. Mix ultra-high molecular weight polyethylene, wood flour, maleic anhydride grafted polyethylene, modified rare earth oxides, amino polysilsesquioxane, nitrile rubber, lubricant and additives, and mix them at 110-120℃ for 3-5 minutes. After cooling to 70-100℃, add foaming agent, continue mixing for 5-10 minutes and calender into sheets. S2. Place the cut sheet material into the mold, heat to 165-175℃, pressurize to 8-15MPa, and hold the pressure for 10-15 minutes. After the heat preservation and pressure holding are completed, quickly release the pressure to obtain a high-strength, impact-resistant, and weather-resistant sheet material.
[0031] By adopting the above technical solution, in step S1, the components such as ultra-high molecular weight polyethylene, modified wood flour, maleic anhydride-grafted polyethylene, modified rare earth oxides, and nitrile rubber are uniformly dispersed and initially plasticized under high-temperature shearing. At the same time, the maleic anhydride-grafted polyethylene is fully melted and plays an interfacial compatibilizing role. Subsequently, the temperature is lowered to 70-100℃ before adding the foaming agent, which effectively avoids the premature decomposition and failure of foaming agents such as azodicarbonamide during the high-temperature mixing stage, ensuring foaming efficiency. The mixing continues for 5-10 minutes and then the mixture is calendered into sheets, so that the foaming agent is evenly distributed in the sheet material.
[0032] In step S2, the sheet material is placed under pressure at 165-175℃ and 8-15MPa for 10-15 minutes to fully melt and plasticize the material and completely fill the mold cavity. Simultaneously, the foaming agent decomposes uniformly under controlled temperature and pressure, generating gas and dissolving in the melt. After the holding pressure is completed, the pressure is rapidly released, causing the gas inside the melt to expand and foam uniformly due to the sudden pressure drop, forming a fine and uniform cell structure. This results in a sheet material that is lightweight, high-strength, has excellent impact resistance, and weather resistance. This process, through temperature gradient control and pressure timing regulation, achieves uniform material dispersion, controllable foaming, and the simultaneous construction of a dense skin and a lightweight core layer. It effectively avoids problems such as premature decomposition of the foaming agent or uneven cell structure caused by traditional one-step mixing, ensuring the mechanical properties and appearance quality of the sheet material.
[0033] In summary, this application has the following beneficial effects: This application improves the tensile strength, flexural modulus, and impact strength of the sheet material by compounding ultra-high molecular weight polyethylene, wood flour, maleic anhydride-grafted polyethylene, modified rare earth oxides, amino polysilsesquioxane, nitrile rubber, lubricant, foaming agent, and additives.
[0034] By synergistically combining ultra-high molecular weight polyethylene (UHMWPE) and nitrile rubber, the elastic deformation of the rubber effectively absorbs impact energy, enhancing notched impact strength and flexural toughness. Maleic anhydride-grafted polyethylene improves the interfacial bonding between wood flour and UHMWPE, allowing the wood flour to act as a reinforcing skeleton. Modified rare earth oxides, uniformly dispersed in ultra-fine particles, promote matrix crystal refinement and orientation regularization through heterogeneous nucleation. Combined with the fiber reinforcement effect of potassium titanate whiskers, this significantly improves tensile strength, flexural modulus, and impact strength. Simultaneously, rare earth elements provide efficient UV shielding, synergistically enhancing weather resistance. Amino polysilsesquioxane forms a dense, low-surface-energy hydrophobic protective layer on the surface, enhancing the board's extremely low water absorption and excellent hydrophobicity. This effectively blocks acid rain erosion and reduces issues such as swelling, cracking, and water seepage and discoloration of the finish. The finish layer can maintain uniform color and stable gloss for a long time without relying on traditional organic coatings, reducing aging phenomena such as chalking, fading, and loss of gloss. This achieves a comprehensive performance of high strength, high impact resistance, and excellent weather resistance and durability. Detailed Implementation
[0035] Preparation Example 1 A modified rare earth oxide is prepared by the following method: 1) Add 100g of nano-La2O3 and 10g of nano-CeO2 to a silane coupling agent ethanol solution (2% by mass of γ-aminopropyltriethoxysilane ethanol solution), soak, filter, and dry to obtain pretreated nano-La2O3. 2) Mix 30g of potassium titanate whiskers, 200ml of N,N-dimethylformamide and 6g of caprolactam, raise the temperature to 60℃, add pretreated nano-La2O3 and nano-CeO2, stir, keep warm for 1h, filter and dry to obtain modified rare earth oxides.
[0036] The average particle size of potassium titanate whiskers is 1 μm; The average particle size of nano-La2O3 is 10 nm, and the average particle size of nano-CeO2 is 5 nm.
[0037] Preparation Example 2 A modified rare earth oxide is prepared by the following method: 1) Add 100g of nano-La2O3 and 15g of nano-CeO2 to a silane coupling agent ethanol solution (2% by mass of γ-aminopropyltriethoxysilane ethanol solution), soak, filter, and dry to obtain pretreated nano-La2O3. 2) Mix 40g of potassium titanate whiskers, 200ml of N,N-dimethylformamide and 8g of caprolactam, raise the temperature to 63℃, add pretreated nano-La2O3 and nano-CeO2, stir, keep warm for 1.5h, filter and dry to obtain modified rare earth oxides.
[0038] The average particle size of potassium titanate whiskers is 3 μm; The average particle size of nano-La2O3 is 50 nm, and the average particle size of nano-CeO2 is 30 nm.
[0039] Preparation Example 3 A modified rare earth oxide is prepared by the following method: 1) Add 100g of nano-La2O3 and 20g of nano-CeO2 to a silane coupling agent ethanol solution (2% by mass of γ-aminopropyltriethoxysilane ethanol solution), soak, filter, and dry to obtain pretreated nano-La2O3. 2) Mix 50g of potassium titanate whiskers, 200ml of N,N-dimethylformamide and 10g of caprolactam, raise the temperature to 65℃, add pretreated nano-La2O3 and nano-CeO2, stir, keep warm for 2h, filter, and dry to obtain modified rare earth oxides.
[0040] The average particle size of potassium titanate whiskers is 5 μm; The average particle size of nano-La2O3 is 100 nm, and the average particle size of nano-CeO2 is 50 nm.
[0041] Preparation Example 4 A modified rare earth oxide, the difference between this embodiment and Example 1 is that caprolactam is not added.
[0042] Preparation Example 5 A modified rare earth oxide, the difference between this embodiment and Example 1 is that nano CeO2 is replaced with an equal weight of nano silicon dioxide.
[0043] Preparation Example 6 A modified rare earth oxide, the difference between this embodiment and Example 1 is that potassium titanate whiskers are replaced with silicon dioxide.
[0044] Preparation Example a A modified wood flour is prepared by the following method: Mix 1200ml of deionized water and ethanol, stir, add 10g of tetraethyl orthosilicate and 200g of wood flour, add ammonia water (5% concentration) dropwise until the pH is 9, stop adding, continue stirring for 5 hours, filter, and take the filter residue to obtain pretreated wood flour; The volume ratio of water to ethanol is 1:1, and the weight ratio of wood flour to the tetraethyl orthosilicate is 1:0.05. The ratio of water and ethanol mixture to wood flour is 1g:6ml; B. Add 200g of pretreated wood flour to 1800ml of cerium sulfate aqueous solution (concentration of 0.1 mol / L), then add 8g of triethylamine and 1g of sodium thiosulfate, heat to 60-65℃, keep warm for 6-8h, filter, and dry to obtain modified wood flour.
[0045] The ratio of pretreated wood flour, cerium sulfate aqueous solution, triethylamine, and sodium thiosulfate was 10g:90ml:0.4g:0.05g.
[0046] Preparation Example b A modified wood flour is prepared by the following method: A. Mix 1400ml of deionized water and ethanol, stir, add 16g of tetraethyl orthosilicate and 200g of wood flour, add ammonia water (concentration of 5%) dropwise until the pH is 9.5, stop adding, continue stirring for 5.5h, filter, take the filter residue, and obtain pretreated wood flour; The volume ratio of water to ethanol is 1:2.5, and the weight ratio of wood flour to the tetraethyl orthosilicate is 1:0.08. The ratio of the water and ethanol mixture to the wood flour is 1g:7ml; B. Add 200g of pretreated wood flour to 2000ml of cerium sulfate aqueous solution (concentration of 0.1 mol / L), then add 24g of triethylamine and 1.6g of sodium thiosulfate, heat to 63℃, keep warm for 7h, filter, and dry to obtain modified wood flour.
[0047] The ratio of pretreated wood flour, cerium sulfate aqueous solution, triethylamine and sodium thiosulfate is 10g:100ml:1.2g:0.08g.
[0048] Preparation Example c A modified wood flour is prepared by the following method: A. Mix 1600ml of deionized water and ethanol, stir, add 20g of tetraethyl orthosilicate and 200g of wood flour, add ammonia water (concentration of 5%) dropwise until the pH is 10, stop adding, continue stirring for 6 hours, filter, take the filter residue, and obtain pretreated wood flour. The volume ratio of water to ethanol is 1:4, and the weight ratio of wood flour to tetraethyl orthosilicate is 1:0.1. The ratio of the water and ethanol mixture to the wood flour is 1g:8ml; B. Add 200g of pretreated wood flour to 2200ml of cerium sulfate aqueous solution (concentration of 0.1 mol / L), then add 30g of triethylamine and 2g of sodium thiosulfate, heat to 65℃, keep warm for 8h, filter, and dry to obtain modified wood flour.
[0049] The ratio of pretreated wood flour, cerium sulfate aqueous solution, triethylamine and sodium thiosulfate is 10g:110ml:1.5g:0.1g.
[0050] Preparation example d A modified wood flour, the difference between this preparation example and preparation example a is that tetraethyl orthosilicate is not added in step A.
[0051] Preparation Example e A modified wood flour, the difference between this preparation example and preparation example a is that the cerium sulfate aqueous solution is replaced with water.
[0052] Example The ultra-high molecular weight polyethylene is selected from Celanese, USA, and its model number is GUR 4150.
[0053] Maleic anhydride-grafted polyethylene is selected from ExxonMobil in the United States, with the grade name 1040.
[0054] The amino-polysilsesquioxane was selected from Shanghai Yuanye Biotechnology Co., Ltd., and its model is aminopropylheptyl-cage-type polysilsesquioxane.
[0055] The nitrile rubber is selected from Lanzhou Petrochemical NBR2907 and needs to be ground to the required particle size.
[0056] Example 1 A high-strength, impact-resistant, and weather-resistant sheet material is prepared by the following method: S1. Mix 600g of ultra-high molecular weight polyethylene, 200g of wood flour, 30g of maleic anhydride-grafted polyethylene, 100g of modified rare earth oxide from Preparation Example 1, 2g of amino polysilsesquioxane, 100g of nitrile rubber, 30g of lubricant (stearic acid) and 10g of additives (white pigment and antioxidant in a weight ratio of 1:3), and knead at 110°C for 3 minutes. After cooling to 70°C, add 10g of foaming agent, continue kneading for 5 minutes, and calender into sheets. The foaming agent is composed of azodicarbonamide and sodium citrate in a weight ratio of 1:0.8; The average particle size of wood flour is 5 μm, the average particle size of modified rare earth oxides is 1 μm, and the average particle size of nitrile rubber is 15 μm. S2. Place the cut sheet material into the mold, heat to 165℃, pressurize to 8MPa, and hold the pressure for 10 minutes. After the heat and pressure holding is completed, quickly release the pressure to obtain a high-strength, impact-resistant, and weather-resistant sheet material.
[0057] Example 2 A high-strength, impact-resistant, and weather-resistant sheet material is prepared by the following method: S1. Mix 700g of ultra-high molecular weight polyethylene, 220g of wood flour, 40g of maleic anhydride-grafted polyethylene, 125g of modified rare earth oxide from Preparation Example 2, 3g of amino polysilsesquioxane, 150g of nitrile rubber, 40g of lubricant (stearic acid) and 20g of additive (white pigment), and knead at 115°C for 4 minutes. After cooling to 90°C, add 15g of foaming agent, continue kneading for 8 minutes and calender into sheets. The foaming agent is composed of azodicarbonamide and sodium citrate in a weight ratio of 1:1; The average particle size of wood flour is 15 μm, the average particle size of modified rare earth oxides is 3 μm, and the average particle size of nitrile rubber is 30 μm. S2. Place the cut sheet material into the mold, heat to 170℃, pressurize to 12MPa, and hold the pressure for 13 minutes. After the heat and pressure holding is completed, quickly release the pressure to obtain a high-strength, impact-resistant, and weather-resistant sheet material.
[0058] Example 3 A high-strength, impact-resistant, and weather-resistant sheet material is prepared by the following method: S1. Mix 800g of ultra-high molecular weight polyethylene, 250g of wood flour, 50g of maleic anhydride-grafted polyethylene, 150g of modified rare earth oxide from Preparation Example 1, 4g of amino polysilsesquioxane, 200g of nitrile rubber, 50g of lubricant (stearic acid), and 30g of additive (white pigment). Mix at 120°C for 5 minutes. After cooling to 100°C, add 20g of foaming agent, continue mixing for 10 minutes, and calender into sheets. The foaming agent is composed of azodicarbonamide and sodium citrate in a weight ratio of 1:1.2; The average particle size of wood flour is 20 μm, the average particle size of modified rare earth oxides is 5 μm, and the average particle size of nitrile rubber is 40 μm. S2. Place the cut sheet material into the mold, heat to 175℃, pressurize to 15MPa, and hold the pressure for 15 minutes. After the heat preservation and pressure holding are completed, quickly release the pressure to obtain a high-strength, impact-resistant, and weather-resistant sheet material.
[0059] Example 4 A high-strength, impact-resistant, and weather-resistant board material is described in this embodiment, which differs from Embodiment 1 in that the wood flour is modified wood flour from Preparation Example a.
[0060] Example 5 A high-strength, impact-resistant, and weather-resistant board material is described in this embodiment, which differs from Embodiment 1 in that the wood flour is modified wood flour from Preparation Example b.
[0061] Example 6 A high-strength, impact-resistant, and weather-resistant board material is described in this embodiment, which differs from Embodiment 1 in that the wood flour is modified wood flour from Preparation Example c.
[0062] Example 7 A high-strength, impact-resistant, and weather-resistant board material is described in this embodiment, which differs from Embodiment 1 in that the wood flour is modified wood flour from Preparation Example d.
[0063] Example 8 A high-strength, impact-resistant, and weather-resistant board material, the difference between this embodiment and Embodiment 1 is that the wood flour is modified wood flour from Preparation Example e.
[0064] Example 9 A high-strength, impact-resistant, and weather-resistant sheet material, which differs from Example 1 in that it is prepared by the following method: 100g of nano-La2O3 and 20g of nano-CeO2 were added to a silane coupling agent ethanol solution (2% by mass of γ-aminopropyltriethoxysilane ethanol solution), soaked, filtered, and dried to obtain modified nano-La2O3.
[0065] Example 10 A high-strength, impact-resistant, and weather-resistant sheet material. The difference between this embodiment and Embodiment 1 is that the modified rare earth oxide is derived from Preparation Example 4.
[0066] Example 11 A high-strength, impact-resistant, and weather-resistant sheet material. The difference between this embodiment and Example 1 is that the modified rare earth oxide is derived from Preparation Example 5.
[0067] Example 12 A high-strength, impact-resistant, and weather-resistant sheet material. The difference between this embodiment and Example 1 is that the modified rare earth oxide is derived from Preparation Example 6.
[0068] Comparative Example Comparative Example 1 A high-strength, impact-resistant, and weather-resistant board material. The difference between this comparative example and Example 1 is that wood flour is replaced with an equal mass of silicon dioxide.
[0069] Comparative Example 2 A high-strength, impact-resistant, and weather-resistant board material. The difference between this comparative example and Example 1 is that the average particle size of the wood flour is 1 μm, the average particle size of the modified rare earth oxide is 1 μm, and the nitrile rubber is 1 μm.
[0070] Comparative Example 3 A high-strength, impact-resistant, and weather-resistant board material. The difference between this comparative example and Example 1 is that the average particle size of the wood flour is 5 μm, the average particle size of the modified rare earth oxide is 1 μm, and the average particle size of the nitrile rubber is 1 μm.
[0071] Comparative Example 4 A high-strength, impact-resistant, and weather-resistant sheet material. The difference between this comparative example and Example 1 is that amino polysilsesquioxane is replaced with an equal weight of silicon dioxide.
[0072] Comparative Example 5 A high-strength, impact-resistant, and weather-resistant sheet material. The difference between this comparative example and Example 1 is that the nitrile rubber is replaced with polyethylene, and the molecular weight of polyethylene is 20,000.
[0073] Comparative Example 6 A high-strength, impact-resistant, and weather-resistant sheet material. The difference between this comparative example and Example 1 is that the modified rare earth oxides are replaced with nano-La2O3 and nano-CeO2, and the weight ratio of nano-La2O3 to nano-CeO2 is 10:1.
[0074] Detection methods / test methods Bending strength: Tested in accordance with GB / T9341-2008; Density: Tested according to GB / T1033.1-2008 (Method A); Tensile strength: Tested in accordance with GB / 71040.2-2022; Impact strength of simply supported beams: tested according to GB / TL043-2008; Aging resistance test: A colorimeter was used to test the color difference of the boards before and after aging. Examples 1-12 and Comparative Examples 1-6 underwent a double 85 test for 500 hours. The experimental data are shown in Table 1. Table 1. Experimental data of Examples 1-12 and Comparative Examples 1-6
[0075] The experimental data above show that the high-strength, impact-resistant, and weather-resistant sheet material prepared by the formula in this application has high strength, high impact resistance, lightweight, and excellent weather resistance stability.
[0076] A comparison of Example 1 and Comparative Examples 1-6 demonstrates that the synergistic use of wood flour, modified rare earth oxides, amino polysilsesquioxane, and nitrile rubber, along with the optimization of the particle size gradient among these three components, is beneficial for improving the strength, impact resistance, and weather resistance of the board.
[0077] A comparison of Examples 1 and 4-5 demonstrates that the modified wood flour prepared in this application can further improve the strength, impact resistance, and aging resistance of the boards.
[0078] A comparison of Examples 1 and Examples 9-12 demonstrates that the modified rare earth oxides prepared in this application can further improve the strength, impact resistance, and weather resistance of the plate material.
[0079] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high-strength, impact-resistant, and weather-resistant sheet material, characterized in that, It is prepared from the following raw materials in parts by weight: 60-80 parts of ultra-high molecular weight polyethylene 20-25 parts wood flour 3-5 parts of maleic anhydride-grafted polyethylene 10-15 parts of modified rare earth oxides 0.2-0.4 parts of amino-polysilsesquioxane 10-20 parts of nitrile rubber 3-5 parts lubricant 1-2 parts of foaming agent 0-3 parts of auxiliary agent; The wood flour has an average particle size of 5-20 μm, the modified rare earth oxide has an average particle size of 1-5 μm, and the nitrile rubber has an average particle size of 15-40 μm.
2. The high-strength impact-resistant and weather-resistant sheet metal according to claim 1, characterized in that, The modified rare earth oxides were prepared by the following method: 1) Add nano-La2O3 and nano-CeO2 to an ethanol solution of silane coupling agent, soak, filter, and dry to obtain pretreated nano-La2O3; 2) Mix potassium titanate whiskers, N,N-dimethylformamide and caprolactam, raise the temperature to 60-65℃, add pretreated nano-La2O3 and nano-CeO2, stir, keep warm for 1-2 hours, filter, and dry to obtain modified rare earth oxides.
3. The high-strength impact-resistant and weather-resistant sheet metal according to claim 2, characterized in that: The weight ratio of the nano-La2O3, the nano-CeO2, the potassium titanate whiskers, and the caprolactam is 10:1-2:3-5:0.6-1.
4. The high-strength impact-resistant and weather-resistant sheet metal according to claim 1, characterized in that: The lubricant includes at least one of oxidized polyethylene wax, PE wax, fatty alcohol dicarboxylic acid ester, and stearic acid.
5. The high-strength impact-resistant and weather-resistant sheet metal according to claim 1, characterized in that, The wood flour is modified wood flour, which is prepared by the following method: A. Mix deionized water and ethanol, stir, add tetraethyl orthosilicate and wood flour, add ammonia dropwise until the pH is 9-10, stop adding, continue stirring for 5-6 hours, filter, take the filter residue to obtain pretreated wood flour; B. Add the pretreated wood flour to a cerium sulfate aqueous solution, then add triethylamine and sodium thiosulfate, heat to 60-65℃, keep warm for 6-8 hours, filter, and dry to obtain modified wood flour.
6. The high-strength impact-resistant and weather-resistant sheet metal according to claim 5, characterized in that: In step A, the volume ratio of water to ethanol is 1:1-4, and the weight ratio of wood flour to tetraethyl orthosilicate is 1:0.05-0.
1.
7. The high-strength impact-resistant and weather-resistant sheet metal according to claim 5, characterized in that: In step B, the ratio of the pretreated wood flour, the cerium sulfate aqueous solution, the triethylamine, and the sodium thiosulfate is 10g:90-110ml:0.4-1.5g:0.05-0.1g.
8. The high-strength impact-resistant and weather-resistant sheet metal according to claim 1, characterized in that: The foaming agent is composed of azodicarbonamide and sodium citrate in a weight ratio of 1:0.8-1.
2.
9. The high-strength impact-resistant and weather-resistant sheet metal according to claim 1, characterized in that: The additives include at least one of antioxidants, colorants, and heat stabilizers.
10. A method for preparing a high-strength impact-resistant and weather-resistant sheet metal as described in any one of claims 1-9, characterized in that, The preparation steps include the following: S1. Mix ultra-high molecular weight polyethylene, wood flour, maleic anhydride grafted polyethylene, modified rare earth oxides, amino polysilsesquioxane, nitrile rubber, lubricant and additives, and mix them at 110-120℃ for 3-5 minutes. After cooling to 70-100℃, add foaming agent, continue mixing for 5-10 minutes and calender into sheets. S2. Place the cut sheet material into the mold, heat to 165-175℃, pressurize to 8-15MPa, and hold the pressure for 10-15 minutes. After the heat preservation and pressure holding are completed, quickly release the pressure to obtain a high-strength, impact-resistant, and weather-resistant sheet material.